Some notes on Putnam and quantum mechanics - García Sanz, Javier (Analysis. Journal of Philosophical Research, 2018)
This article reviews the most relevant contributions made by Hilary Putnam to the interpretation of Quantum Mechanics, specifically to the so-called “measurement problem”. We discuss his ideas regarding the apparent non-applicability of the quantum rules to the macroscopic world and the emergence of the Born rule, which determines the probabilistic nature of the quantum world. Some of the logical studies of Putnam are also reviewed due to their special relevance to the novel field of quantum computation.